Women's health in mid-life : a primary care guide - Rosenfeld, Jo Ann (Cambridge, 2004)
This book addresses the major healthcare issues of women in their midlife, between the ages 40 to 65. This is a time of challenge and an opportunity for preventive healthcare. Written by 20 primary care physicians, this book will help family practitioners provide the best possible healthcare for these women.